Responsible care : a new strategy for pollution prevention and waste reduction through environmental management - Cheremisinoff, Nicholas P. (Gulf Pub. Co., 2008)
Environmental regulations provide protection to the public, workers and the environment. To protect themselves from long-term liabilities, however, companies have to do more than just comply with the basic responsibilities. This handbook is designed to introduce terminology, methodology, tools, procedures and practical guidance for incorporating efficient pollution prevention strategies into the overall business plan. It is a company's responsibility to protect and control its management of waste and pollution, and a company that fails to do so will ultimately inflict a negative impact on its bottom line, especially in financial performance. Responsible Care delivers critical guidelines and rules of thumb required for industrial managers to improve their companies' profitability through waste reduction, cleaner production technologies and sound management practices.
Keywords: Pollution prevention.; Waste minimization.; Environmental responsibility.; Environmental management.; Social responsibility of business.; Environmental protection -- Case studies.; Source reduction (Waste management); elektronické knihy; electronic books